GENDER DIFFERENCES IN LANGUAGE LEARNING STYLE AND LANGUAGE LEARNING STRATEGIES - Viriya, Chayata; Sapsirin, Sutthirak (Indonesian Journal of Applied Linguistics, 2014)
Abstract: This paper seeks to investigate the gender differences in language learning style and language learning strategies. The study used the perceptual learning-style preference questionnaire (PLSPQ) to investigate the learning style preferences and the Strategy Inventory for Language Learning (SILL) version 7.0 designed by Oxford (1990) to find the learning strategy preferences of first year University students at the faculty of Information and Communication Technology (ICT) in Thailand. These were administered to 150 learners. The results indicate that gender does have effects on language learning style but there is no effect on language learning strategies. The implication of the results for language teachers and learners are also presented.Keywords: language learning style, language learning strategies, genderÂ PERBEDAAN-PERBEDAAN GENDER DALAM GAYA BELAJAR BAHASA DAN STRATEGI-STRATEGI BELAJAR BAHASA Â Abstrak: Makalah ini berusaha untuk menyelidiki perbedaan-perbedaan gender dalam gaya belajar bahasa dan strategi-strategi belajar bahasa. Kajian ini menggunakan angket pilihan gaya belajar perseptual (the perceptual learning-style preference questionnaire (PLSPQ)) untuk menyelidiki pilihan-pilihan gaya belajar dan Inventaris Strategi untuk Belajar Bahasa (the Strategy Inventory for Language Learning (SILL)) versi 7.0 yang dirancang oleh Oxford (1990) untuk menemukan pilihan-pilihan strategi belajar mahasiswa Universitas di Fakultas Teknologi Komunikasi dan Informasi. Angket-angket tersebut diberikan pada 150 pembelajar. Hasilnya menunjukkan bahwa gender memang memiliki pengaruh terhadap gaya belajar bahasa, tapi tidak berpengaruh pada strategi-strategi belajar bahasa. Implikasi dari hasil ini bagi para guru dan pembelajar bahasa juga dihadirkan.Kata kunci: Gaya belajar bahasa, strategi-strategi belajar bahasa, gender